Evaluasi Strategi dalam Meningkatkan Kualitas Pelayanan Publik di Unit Pelaksana Penimbangan Kendaraan Bermotor (UPPKB) Kemang Kabupaten Bogor - Rifky Rahman; Akhmad Hidayat Rahadian (Neraca : Jurnal Akuntansi Terapan, 2025)
This study evaluate the strategies to improve public service quality at UPPKB Kemang, Bogor Regency, using a qualitative approach. The research was conducted at UPPKB Kemang, with data collected through observation, interviews, and documentation. The findings indicate that an effective strategy for improving service quality is implementing the Online Weighbridge System (JTO). To minimize obstacles, UPPKB carries out regular maintenance, calibration of weighing instruments, and provides a backup generator. Socialization efforts are also conducted to educate drivers and transportation companies on the importance of compliance with weighing regulations. Infrastructure improvements, such as optimizing JTO services and upgrading weighing station facilities, help streamline operations. Additionally, UPPKB strengthens collaboration with relevant institutions to ensure regulations are effectively enforced without disrupting freight transport operations. These strategies are designed to enhance service quality and efficiency at UPPKB Kemang, Bogor Regency.